Resveratrol as an Anti-Asthmatic Agent: Could This Stilbenoid Help Against Covid-19 in Any Way? a Meta-Analysis [Resveratrol Como Agente Antiasmático: ¿Podría Este Estilbenoide Ayudar Contra el Covid-19 de Alguna Manera? Un Metaanálisis] - Martinez-Salinas, J; Morales-Munoz, B; Jaimes-Fernandez, L (MS-Editions, 2021)
Resveratrol is a phenolic phytoconstituent found in many plants. This molecule has always caught the attention of scientists because of biological potentials such as inhibition of inflammation, oxidative stress and platelet aggregation as well as to prevent/protect against cardiovascular and neurodegenerative disease/disorders. Literature search have been conducted over resveratrol in covid-19 and asthma studies published in Pubmed and Google Scholars until 30 September 2020. The criteria used in the literature review were determined and were reviewed works on resveratrol including 368 articles and 47 articles on covid-19 and asthma, respectively. As a result of meta-analysis, TNF-α values of the studies showed a significant difference (heterogeneity) of I2=68.39% from each other in total (Cohran Q:6.33, p<0.0423). This study shows that resveratrol would have a potential to reduce ARDS symptoms, by suppressing the cytokine storm and severe inflammation caused by SARS-CoV-2, and by showing strong activity against various types of DNA/RNA viruses. © 2021, MS-Editions. All rights reserved.